Peningkatan Efisiensi Produksi Baglog Melalui Percepatan Waktu Siklus Produksi di Usaha Lancar Abadi Pendekatan Critical Path Method - NI MADE KENCANA MAHARANI; IGA OKA SURYAWARDANI; I NYOMAN GEDE USTRIYANA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2016)
Abstract The Enhancement of Baglog Production Efficiency through Acceleration Time of Production Cycle Critical Path Method Approach Lancar Abadi Company which has produced oyster mushrooms media (baglog) is involving many business players. The research objectives are to find out (1) mechanism of Supply Chain Management; (2) actual time and critical path on one cycle of production through Critical Path Method; and (3) crush time due to addition cost through Critical Path Method. The research uses descriptive quantitative method with model Performance of Activity approachment and Critical Path Method. Cost, time, capacity, and capability dimentions in Performance of Activity has been used to described performance activities that are part of the process in Supply Chain Management. The results show that (i) the baglog materials has been directly bought to the company by the suppliers, meanwhile, baglog had been directly obtained by the consumer through making an order to the Lancar Abadi Company; (ii) The selected critical path consisting of the preparation, sifting, composting, draining, mixing, filling, until the mycelium growth with total 514 hours/cycle (iii) By the addition of acceleration cost about Rp262.968,98, the company was able to speed up the production cycle about 32,57 hours (1.36 days). So that, company will be able to increase the additional 1.12 production cycle times/year which was equivalent to 899 baglog/year. Keyword : Critical path method, supply chain management, baglog, performance of activity